Adaptive Shifts: Identity and Genre in the Memorials of the 1820 British Settlers in the Cape Colony - Włodarczyk, Matylda (Department of Dutch and South African Studies, Faculty of English, 2010)
Multiple reflections of social transformation are to be found within newly founded colonial communities, such as that of the early British settlers in South Africa (known as the ‘1820 Settlers’) analysed in this study. Such reflections include indications of the genre transformations which may be traced in the 1820 Settler letters (petitions/memorials) addressed to the officials responsible for the colonial plan (1819-1825). Prior to the colonisation, for instance, this genre was clearly devoid of an affective component (Besnier 1990: 431; cf. also Katriel 2004: 4) which has surfaced in the colonial context. On a micro-level, it is echoed in, among others, the strategies of reporting speech which is understood here as a marker of stance (Włodarczyk 2007; cf. Biber 2004; Besnier 1993). The proposed features of genre transformation are illustrated here in the course of a linguistic comparison of two collections of letters presented in the paper. As example, some innovations are introduced in the correspondence of Jane Erith, a destitute settler whose property was destroyed in a fire and who sought support from the colonial authorities. In her writing, as a desperate colonial subject she confronts the disastrous inadequacy of the institutional sources of power as a way of resisting the established power relations (cf. e.g. Laidlaw 2005). The paper demonstrates that some connections between genre conventions and social upheaval may be revealed in the course of linguistic analysis.
Keywords: genres; petition; 1820 settlers; colonisation; affect; reported speech